2019
DOI: 10.1002/adhm.201900702
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Effects of Injectable Biodegradable Thermogels on Pharmacotherapy of Inflammatory Glaucoma‐Associated Degradation of Extracellular Matrix

Abstract: 111.8 million people worldwide by 2040. [1] High intraocular pressure (IOP) has been considered the major indicator for diagnosing glaucoma, and the reduction of elevated IOP is the current clinical approach used to prevent disease progression. [2] Several models of glaucoma have indicated that inflammatory components can directly link elevated IOP with retinal degeneration. [3][4][5][6] As a result, the expression of inflammatory molecules, including nitric oxide, [7] interleukins (ILs), [8] p38 MAPK, [9] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…In this context, polyamidoamine (PAMAM) dendrimers have been explored in PNIPAAm/gelatin thermo-responsive carriers because they are biodegradable and regulate the inflammatory response. 131 This study showed that the drug release profile and anti-inflammatory effects were strongly influenced by the generation of PAMAM dendrimers. Due to the specific structure of the third generation of the PAMAM dendrimers, such as sufficiently large interior cavities and an adequate number of amine surface groups, the synergistic effects in the PNIPAAm-gelatin copolymer can be optimized.…”
Section: Beyond Sustained Drug Releasementioning
confidence: 90%
“…In this context, polyamidoamine (PAMAM) dendrimers have been explored in PNIPAAm/gelatin thermo-responsive carriers because they are biodegradable and regulate the inflammatory response. 131 This study showed that the drug release profile and anti-inflammatory effects were strongly influenced by the generation of PAMAM dendrimers. Due to the specific structure of the third generation of the PAMAM dendrimers, such as sufficiently large interior cavities and an adequate number of amine surface groups, the synergistic effects in the PNIPAAm-gelatin copolymer can be optimized.…”
Section: Beyond Sustained Drug Releasementioning
confidence: 90%
“…Ophthalmic applications of intravitreal injectable drug-loaded hydrogels for glaucomic treatment to the posterior section of the eye have been shown to overcome ocular barriers and effectively treat glaucoma [132,133]. This novel drug delivery system has properties of good adherence and viscosity, and achieves the objective of retention and therapeutic treatment of ocular diseases in the most remote areas of the eye.…”
Section: Intravitreal Administration Of Injectable Drug-loaded Hydrog...mentioning
confidence: 99%
“…All prepared copolymeric carriers exhibit a relevant intraocular pressure-lowering and an excellent miotic effect [ 111 ]. Afterward, Nguyen and colleagues prepared injectable biodegradable thermogels coloaded with pilocarpine and ascorbic acid [ 112 ]. The synthesized gel obtained the double effect of lowering elevated IOP and reducing stromal collagen degradation in inflammation-induced glaucoma.…”
Section: Drug Deliverymentioning
confidence: 99%